Perluasan Teori Maqashid Al-Syari’ah: Kaji Ulang Wacana Hifdz Al-‘Ummah A. Djuzuli - Syahrial Dedi (Institut Agama Islam Negeri Curup, 2016)
This paper wasdone the discourse of “hifdz al-'ummah/the savior of nation” of A. Djazuli in the theory of “maqashid al-shari'ah”. Because the benefit is the essence or substance of Islamic law.Mentioning the essence or substance of Islamic law intended to mean that the beneficiaries are a key element of the building of Islamic law, which binds other related ones. The data presented in this paper comes from primary sources directly related to A. Djazuli thought. This study found that the study of “maqashid al-shari'ah/the purpose of law” which is now developing emphasize to people as individual and less offset by humans as members of the community. The concept of people becomes important in life togetherwhether people within the scope of the first, second, or third which are well aligned with the economic, political, and social-culture aspects of a nation or the international community. In the era of globalization, the roles of aspects become very strong and their interaction becomes very intensive.